Peranan Pendidikan Agama Hindu Dalam Penguatan Karakter Di SMP Negeri 1 Bangli - Cahya Purnama, Sang Putu Gede (Jayapangus Press, 2024)
The crucial role of Hindu religious education in the school context is manifested in the formation of students character, including moral, ethical, and spiritual dimensions. The aimed at investigating the contribution of Hindu religious education in strengthening students character at SMP N 1 Bangli. The research method applied is a qualitative approach using data collection techniques through observation, interviews, and document analysis. The results stated that Hindu religious education at SMP N 1 Bangli makes a significant contribution to the development of students character. This learning material provides a deep understanding of spiritual, ethical, and moral values in Hinduism. The role of Hinduism teachers is very important as the main mentor who help students understand and internalise these teachings in everyday life. Hindu religious education at SMP N 1 Bangli is not only provides theoretical knowledge about religious teachings, but also encourages students to apply these values in their daily activities. Therefore, continuous efforts to improve the quality of Hindu religious education need to be made in order to provide a broader positive impact on the development of students' character in the school environment.